2017
DOI: 10.1098/rsob.160334
|View full text |Cite
|
Sign up to set email alerts
|

Atypical centrioles are present in Tribolium sperm

Abstract: Typical centrioles are made of microtubules organized in ninefold symmetry. Most animal somatic cells have two centrioles for normal cell division and function. These centrioles originate from the zygote, but because the oocyte does not provide any centrioles, it is surprising that the zygotes of many animals are thought to inherit only one centriole from the sperm. Recently, in the sperm of Drosophila melanogaster, we discovered a second centriolar structure, the proximal centriole-like structure (PCL), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…Since centrioles do not normally have central microtubules, it was later proposed that the base of the axoneme of Tribolium is not an axoneme, but rather a centriole. This hypothesis was confirmed when it was shown that the base of the axoneme contains the centriole specific protein Ana1 [ 10 ].…”
Section: The Diverse Types Of Distal Centriolesmentioning
confidence: 85%
See 4 more Smart Citations
“…Since centrioles do not normally have central microtubules, it was later proposed that the base of the axoneme of Tribolium is not an axoneme, but rather a centriole. This hypothesis was confirmed when it was shown that the base of the axoneme contains the centriole specific protein Ana1 [ 10 ].…”
Section: The Diverse Types Of Distal Centriolesmentioning
confidence: 85%
“…Such minimal centrioles were recently identified in the spermatozoon of insects and non-rodent mammals ( Figure 3 ) [ 9 , 10 , 11 , 12 ]. These centrioles are smaller, have reduced protein composition, and have either no microtubules or have microtubules that lack nine-fold symmetry.…”
Section: Spermatozoa Have Specialized Centriolesmentioning
confidence: 95%
See 3 more Smart Citations